Pattern recognition : ACPR 2019 Workshops, Auckland, New Zealand, November 26, 2019, Proceedings /: ACPR 2019 Workshops, Auckland, New Zealand, November 26, 2019, Proceedings. (2020) - Unknown
No abstract available